ChemInform Abstract: Organocatalytic, Difluorocarbene‐Based S‐Difluoromethylation of Thiocarbonyl Compounds. Issue 26 (June 2015) - Fuchibe, Kohei; Bando, Masaki; Takayama, Ryo; Ichikawa, Junji
Abstract Difluorocarbene generated in situ acts as difluoromethylating agent of thioamides and thiocarbamates.